Pengaruh Efektivitas E-Commerce Terhadap Profitabilitas dan Pelayanan Konsumen By Sarah Ahmad - Muhammad Rivaldi; Rifky Permana (CV. ITTC INDONESIA, 2024)
Technological advancements drive product marketing innovation, facilitating competition in the market. Technology simplifies consumer-seller interaction and enhances understanding of e-commerce in Indonesia. By Sarah Ahmad, a beauty care business in South Jakarta, uses websites, e-commerce, and marketplaces like Shopee to streamline transactions and improve cost, labor, and time efficiency. This study employs SPSS to process and analyze data collected through Observation, Questionnaires, and Interviews. Primary data comes from Google Form questionnaires and employee interviews, while secondary data is sourced from books, e-books, and journals. The Cobit 5 framework is used to assess maturity levels, showing that the DSS01 (Manage Operations) and DSS02 (Manage Service Request and Incident) domains have exceeded targets, with positive GAP values. The audit results using Cobit 5 demonstrate the effectiveness of e-commerce in boosting profitability and customer service. The average maturity level for DSS domains being above target reflects strong performance. Future research could explore other Cobit 5 domains. A quantitative Cobit 5 audit of Shopee's e-commerce system at By Sarah Ahmad shows DSS01 having the highest Maturity Level of 17.62 and DSS02 at 12.79, both exceeding the target level 4, indicating the effectiveness of Shopee in product sales and customer service at By Sarah Ahmad